2013
DOI: 10.1007/s00167-013-2731-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intentional femoral component flexion in navigated TKA on gap balance and sagittal anatomy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Previous cadaver and clinical studies could not separate the effect of FFC from that of other possible confounding variables (e.g. PCO), and have shown contrasting results [ 5 , 6 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cadaver and clinical studies could not separate the effect of FFC from that of other possible confounding variables (e.g. PCO), and have shown contrasting results [ 5 , 6 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that 1 of flexion is around 1e1.5 mm decrease of flexion gap. 18,19 This correlation is shown in Fig. 3.…”
Section: New Techniques For Ligament Balancingmentioning
confidence: 64%
“…In the first years, navigation could show that it is able to improve coronal alignment from 61% to 75% up to 91%-96% within the 3°corridor. [1][2][3] Even in Indian population with severe deformities those results could be confirmed. 4 Over the following years alternative techniques, like patient specific instrumentation had been introduced however never reached this high accuracy.…”
Section: Navigation/robotics/aimentioning
confidence: 71%